PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP SEMANGAT KERJA PEGAWAI PADA BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH ( BAPPEDA ) KOTA BIMA - M. Fuadin; Sri Ernawati (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This type of research is associative with a quantitative approach. The population in this study was 51 people, with a sampling technique using purposive sampling based on certain criteria. the sample in this study were 38 respondents. Data collection includes observation, questionnaires, documentation and literature study using a Likert scale. using data analysis techniques in the form of validity test, reliability test, simple linear regression analysis test, simple coefficient of determination test, simple correlation coefficient test, and t test. The results of this study indicate that the variable work characteristics affect employee morale At The Regional Planning And Development Agency (BAPPEDA) Bima City